THE CORONAVIRUS PANDEMIC AND EUROPE’S UNDECLARED ECONOMY: IMPACTS AND A POLICY PROPOSAL (The South East European Journal of Economics and Business, 2020)
The coronavirus pandemic has led to a loss of revenues for enterprises and workers due to workplace closures and restrictions on movement to ‘flatten the curve’. In response, governments have made available temporary financial support to enterprises and workers affected. This paper evaluates a group currently excluded from this support, namely enterprises and workers in the undeclared economy, and a possible government policy response. To identify those involved, a 2019 Eurobarometer survey of undeclared work in Europe is reported. This reveals that one in every 132 European citizens relies wholly on undeclared earnings and the sectors and population groups involved. Given their reduced revenues and inability to access the temporary financial support, a voluntary disclosure initiative is recommended which brings undeclared enterprises and workers into the declared economy and onto the radar of state authorities by offering access to this temporary financial support if they disclose their previous undeclared work.